Isolation and characterization of circulating tumor cells using a novel workflow combining the CellSearch® system and the CellCelector™ - Neumann, Martin H. D.; Endris, Volker; Weichert, Wilko (Biotechnology progress, 2017)
Circulating tumor cells (CTC) are rare cells which have left the primary tumor to enter the blood stream. Although only a small CTC subgroup is capable of extravasating, the presence of CTCs is associated with an increased risk of metastasis and a shorter overall survival. Understanding the heterogeneous CTC biology will optimize treatment decisions and will thereby improve patient outcome. For this, robust workflows for detection and isolation of CTCs are urgently required. Here, we present a workflow to characterize CTCs by combining the advantages of both the CellSearch® and the CellCelector™ micromanipulation system.